Murders Committed with Particular Cruelty: Current State and Development Trends in the Republic of Kazakhstan and the Kyrgyz Republic - DOSSUMOV, Serimzhan Tuleuovich (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
In this paper statistics are given with the number of victims due to murders committed with particular cruelty in Kazakhstan and Kyrgyzstan for the period from 1998 to 2015. These data eloquently testify that the problem is topical both for the above countries and for the whole world. The main objectives of the work are to analyze committed crimes, identify their motives and develop effective recommendations for minimizing such crimes in society and their prevention. The author created this work based on the modern researches and statistics.